2021
DOI: 10.1021/acschemneuro.1c00124
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Functional Characterization of 2-(2,5-Dimethoxyphenyl)-N-(2-fluorobenzyl)ethanamine (25H-NBF) Positional Isomers

Abstract: Serotonergic psychedelics, substances exerting their pharmacological action through activation of the serotonin 2A receptor (5-HT 2A R), have continuously comprised a substantial fraction of the over 1000 reported New Psychoactive Substances (NPS) so far. Within this category, N-benzyl derived phenethylamines, such as NBOMes and NBFs, have shown to be of particular relevance. As these substances remain incompletely characterized, this study aimed at synthesizing positional isomers of 25H-NBF, with two methoxy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 26 publications
(65 reference statements)
4
19
0
Order By: Relevance
“…This fact is supported by the data that we have published earlier 25,26 and also published by Jensen et al 27 Within the NBF group itself, all positional isomers exhibit high affinity to the 5‐HT 2A receptor (24H‐ ≈ 25H‐ ≈ 26H‐ ≥ 23H‐ ≥ 35H‐ and 34H‐NBF; Table 1). 26 …”
Section: Introductionsupporting
confidence: 83%
See 4 more Smart Citations
“…This fact is supported by the data that we have published earlier 25,26 and also published by Jensen et al 27 Within the NBF group itself, all positional isomers exhibit high affinity to the 5‐HT 2A receptor (24H‐ ≈ 25H‐ ≈ 26H‐ ≥ 23H‐ ≥ 35H‐ and 34H‐NBF; Table 1). 26 …”
Section: Introductionsupporting
confidence: 83%
“…In vitro study of some groups of N ‐(2‐substituted benzyl)phenethylamines showed that the affinity to the 5‐HT 2A receptor decreases in the row: NBOMe ≈ NBOH > NBMD > NBF 19–24 . This fact is supported by the data that we have published earlier 25,26 and also published by Jensen et al 27 Within the NBF group itself, all positional isomers exhibit high affinity to the 5‐HT 2A receptor (24H‐ ≈ 25H‐ ≈ 26H‐ ≥ 23H‐ ≥ 35H‐ and 34H‐NBF; Table 1). 26 …”
Section: Introductionsupporting
confidence: 69%
See 3 more Smart Citations